STRATEGY FOR OPTIMIZING INVESTMENTS IN HUMAN CAPITAL (Universal International Scientific Journal, 2026)
This article analyzes the role of human capital in sustainable development and its interaction with other forms of capital. Financial, natural, productive, social and human capital are considered as the main components that ensure sustainability. The results of the study show that investments in human capital accelerate economic growth through education and health systems, reduce poverty and increase social well-being. Human capital is an important economic and social asset that includes the knowledge, skills, health and creative potential of each person. In order to achieve success in the modern economy, it is very important to invest not only in financial capital, but also in human capital. In this article, we will consider strategies for effectively optimizing investments in human capital
Keywords: human capital; investment; sustainable development